(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe clinical, paraclinical features and treatment results of borderline ovarian tumors at the National Hospital of Obstetrics and Gynecology. Materials and research methods: Sample size: 88 patients during 5 years from January 1, 2018 to December 31, 2022. Methods: Retrospective descriptive study. Results: The proportion of serous, mucinous and other types of tumors was 50%, 38% and 12% respectively. The average age was 36.07, the 30 - 39 year old group accounted for the highest proportion. Lower abdominal pain was the most common symptom (43.2%). Most ovarian tumors were borderline on one side, painless and movable. 54,5% tumors > 10 cm and the size of mucinous tumors was statistically significantly larger than that of serous tumors. On ultrasound, the rate of septa was 47.7%, papillae was 35.2%, solid tissue was 35.2%, and mixed sound was 60.2%. The abnormal CA -125 value was 56.8%, decreasing rapidly after surgery and chemotherapy. The rate of conservative surgery was 77.2%, of radical surgery was 21.8% and of second surgery was 11.3%. Conclusion: Boderline ovarian tumors may have some malignant characteristics. Surgery is an effective treatment method and conservative surgery is increasingly widely applied.